THE PRINCIPLES OF DISTINCTION AND PROPORTIONALITY REGARDING ATTACK ON THE INDONESIAN HOSPITAL IN GAZA BY ISRAEL DEFENSE FORCE (IDF) - Affazul Muna, Inas (JIL : Journal of Indonesian Law, 2025)
This study analyzes the Israel Defense Force (IDF) attack on the Indonesian Hospital in Gaza in November 2023 through the application principles of distinction and proportionality in International Humanitarian Law (IHL). The method used is normative legal research with legislative, conceptual, and case-based approach based on the 1949 Geneva Convention, the 1977 Additional Protocol I, and the 1998 Rome Statute. The results of the study show that there is no independent evidence verify claims of IDF that hospital was used Hamas for military purposes. The attack resulted damage to medical facilities, civilian casualties, and disruption of health services, which had widespread impact on the people of Gaza. The analysis shows that action of IDF did not comply with the principle of distinction because hospitals remain protected civilian objects, and violated the principle of proportionality because the civilian casualties caused far exceeded presumed military advantage. Thus, these attacks could potentially be classified as serious violations of IHL and constitute war crimes.